Designing Horizontality. - Viganò, Paola; Pietropolli, Tommaso (Taylor & Francis, 2021)
This paper is divided into three parts. The first introduces a trilogy of concepts and figures of the discourse. The concept of isotropy, as opposed to hierarchy, evokes the same conditions in all directions. The concept of porosity tackles the fluidity and malleability of space, the passage of bodies through other bodies. The concept of horizontality, in turn, explores the possibility of different types of spatial order. The trilogy presents a critical approach and a discourse on the possibility of a project which, in relation to the current urbanisation process and current debate, can be considered a counter project. The second part concentrates on horizontality, investigating its constructive role in the organisation of spatial thought. As opposed to the vertical/hierarchical organisation of space, horizontal and acentred structures enable the dissolution of the centre/periphery dichotomy, while addressing questions of inter-species spatial equity and individual/collective emancipation. The third part of the paper introduces a series of actual cases of territorial design where the idea of horizontality, against the background of the entire conceptual trilogy, was operational. Here space is considered not as a neutral connector, but as a support and an agent of horizontality. The order of the three parts must not be misunderstood. It does not refer to a research sequence where first comes theoretical thinking, then this is embedded into a tradition to legitimate it and finally applied to case studies. Our discourse is produced through the interpretation, projections and design of concrete situations. It is from the constant exchange among the three different levels that the figures have arisen. This inversion is always to be considered when reading the following text, the order of which is only instrumental in a better explanation of the discourse itself.
Keywords: Planungstheorie; Planungsphilosophie; Hierarchie; Planungsebene; Raumstruktur; Räumliche Disparität; Raumorganisation; Praxisbeispiel; Großstadtregion; Horizontalität